Bioelectrochemical Systems As Tools To Study Subsurface Biogeochemical Processes - Friedman, Elliot (2014)
Microbes capable of extracellular electron transfer have been identified, characterized, and isolated from a wide variety of environments, including many soils and sediments. These uniquely-adapted microbes have been extensively studied in bioelectrochemical systems, such as microbial fuel cells, microbial electrolysis cells, and microbial three-electrode systems. These bioengineered systems capitalize on their ability to respire with insoluble electron acceptors, including solid-state electrodes. However, the role that these microbes play within the microbial community and biogeochemistry of the soils and sediments in which they are naturally found is less clear. Subsurface microbial communities perform many functions, including: degrading organic matter, controlling carbon and nutrient availability for primary producers, producing greenhouse gases, and mitigating anthropogenic pollutants. Therefore, it is critical to understand the complex community dynamics that govern soil microbiome structure in subsurface environments, and to link microbial processes with landscape level ecosystem function. To this end, I developed a cost-effective and field-ready potentiostat, capable of long-term operation in remote areas with poised subsurface electrodes and measuring respiration of iron- and humic acid-reducing microbes. I integrated these systems with measurements of greenhouse gas emission from soils and characterization of microbiome structure to link the microbial and landscape scales. I applied these techniques to two environments: (1) Arctic peat soils outside Barrow, Alaska to study the impacts of dissimilatory metal-reduction and microbial community structure on greenhouse gas emissions; and (2) sediments in a riparian zone near Ithaca, New York to study differences in biogeochemistry across hydrologic and spatial gradients. In the Arctic, potentiostatic monitoring of bacterial respiration revealed a correlation with soil temperature and the activation of microbes at deeper depths as the thaw progressed. ...